Occupational asthma caused by cellulase and lipase in the detergent industry. Issue 9 (18th August 2004) - Brant, A; Hole, A; Cannon, J; Helm, J; Swales, C; Welch, J; Newman Taylor, A; Cullinan, P
Abstract : Three employees from two different detergent companies were investigated for occupational asthma, using skin prick tests, serum specific IgE, and specific bronchial challenge. Two were challenged with lipase and one with cellulase. All three cases had immunological evidence of sensitisation to the detergent enzymes with which they worked. Bronchial challenge in each provoked a reproducible dual asthmatic response, which reproduced their work related symptoms. These are the first reported cases of occupational asthma attributable to cellulase and lipase in the detergent industry. Four of the most common enzymes used in this industry have now been reported to cause occupational asthma; continued vigilance and caution are needed when working with these or other enzymes.